Extracellular Vesicles: Biology and Potentials in Cancer Therapeutics - Cho, William (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Extracellular vesicles (EVs) are particles wrapped in a lipid bilayer membrane and are naturally released from cells. This kind of cargo vessel is a nanostructure that mainly transfers lipids, proteins, various nucleic acid fragments, and metabolic components to neighboring cells or distant parts of the body through the circulatory system. EVs are of great significance to the communication mechanism between cells. This book collects feature articles to enhance our understanding of the biological characteristics of EVs and their potential applications.